Field evaluation of Populus deltoides clones for growth traits and tolerance to leaf spots - Singh, Lakhwinder; Tak, Parminder Singh; SINGH, GURVINDER PAL (Indian Forester, 2022)
The study was conducted to evaluate the growth characters of the 16 clones of Populus deltoides under field conditions at the Main Experimental Area, Department of Forestry and Natural Resources, Punjab Agricultural University, Ludhiana following Randomised Complete Block Design with four replication and plot size of four trees. Significant variation was noticed among the clones for tree height, diameter and wood volume. Clones L-48/89, 9607, L-47/88, 9607 and 6503 Â were observed to be most promising for wood productivity. The poplar clones were found susceptible to leaf spots caused by Cercospora populina, Alternaria alternate, Drechslera sp. and Rhizoctonia sp. Clone L-48/89 with least leaf spots severity of 6.9 per cent was categorized as moderately resistant along with clone L-47/88, 9607 and T-50. Moderate susceptibility response against leaf spots was observed in clone T-59, G-48 and 5503. None of the clones exhibited resistant reaction to leaf spots.